Effects of Mango Seed (Mangifera indica) Powder on Growth Performance, Immune Response, Gut Morphology, and Gene Expression of Nile Tilapia (Oreochromis niloticus) - Camilla Maria Fontana; Md Afsar Ahmed Sumon; Supreya Wannavijit; Anisa Rilla Lubis; Nuttapon Khongdee; Nguyen Vu Linh; Yuthana Phimolsiripol; Seyed Hossein Hoseinifar; Hien Van Doan (Fishes)
This study explored the effects of mango seed (MS) powder supplementation on the growth, immune response, gene expression, and intestinal morphology of Nile tilapia (Oreochromis niloticus) over an 8-week period. A total of 300 Nile tilapia fingerlings (average weight of 15.29 ± 0.05 g) were divided into five treatment groups and fed either a basal diet or one of four experimental diets containing MS powder at concentrations of 10 (MS10), 20 (MS20), 40 (MS40), and 80 (MS80) g kg−1. The results demonstrated that Nile tilapia fed MS-supplemented diets experienced significant improvements (p < 0.05) in weight gain (WG), specific growth rate (SGR), and survival rate (SR) compared to the control group (0 g kg−1 MS). The MS-treated groups also showed a significant increase (p < 0.05) in the height and branching of intestinal villi along the entire length of the intestine, as well as a significantly higher villus-to-crypt depth ratio (V/C), indicating enhanced intestinal health and functionality. Moreover, although MS supplementation did not increase peroxidase activity, it did lead to a significant increase (p < 0.05) in the activity of skin mucus and serum lysozyme, along with upregulated gene expression of immune-related (IL-1, IL-8, and LBP) and antioxidant genes (GST-α, GPX, and GSR). Polynomial regression analysis identified an optimal MS dosage of 36.43–45 g kg−1 for effectively improving growth, immunity, and immuno-oxidant gene expression in Nile tilapia. These results emphasize mango seed (MS) as a promising natural supplement for improving the diet of Nile tilapia and, potentially, other freshwater fish widely used in aquaculture.